2015
DOI: 10.1007/s13277-015-3705-7
|View full text |Cite
|
Sign up to set email alerts
|

Chemokines and their receptors in esophageal cancer—the systematic review and future perspectives

Abstract: Esophageal cancer (EC) is an aggressive malignant solid tumor with rapid progression and unfavorable prognosis. The 5-year survival rate for EC patients was estimated to be less than 10 %. Therefore, there is an urgent need to improve diagnostic tool and effective treatment therapies for EC patients. In our paper, the general structure and function of chemokines and their receptors as well as their role in cancer progression were shortly presented. Moreover, the aim of our paper was to summarize and refer the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…In recent years, chemokines have been found to be involved in different cellular biological processes, such as cell proliferation, differentiation, apoptosis, and migration (8)(9)(10). Moreover, they are also found to be deregulated in various human types of cancer (11,12). For instance, CXCL12, an important chemokine, has been found to be highly expressed in lung cancer tissues and is associated with lung metastasis (13).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, chemokines have been found to be involved in different cellular biological processes, such as cell proliferation, differentiation, apoptosis, and migration (8)(9)(10). Moreover, they are also found to be deregulated in various human types of cancer (11,12). For instance, CXCL12, an important chemokine, has been found to be highly expressed in lung cancer tissues and is associated with lung metastasis (13).…”
Section: Introductionmentioning
confidence: 99%
“…The main significance of chemokines and their receptors in tumor development is facilitating the invasion and metastasis of malignant cells, including adherence, proliferation, extravasation from blood vessels, angiogenesis, and protection from the host response [ 1 5 ]. Some authors suggested the potential role of selected chemokines and/or their receptors in the development of various types of tumors, including EC [ 15 19 ]. These neoplasms are characterized by poor prognosis of patients' survival.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is increasing evidence that CXCL12 and its specific receptor CXCR4 play an important role in many steps of tumor progression, such as invasion, migration, and proliferation of malignant cells. Some authors indicated that CXCL12 and its receptor CXCR4 were expressed in EC tissue and significantly correlated with invasion, angiogenesis, lymph node, and metastasis as well as prognosis of EC patients' survival [ 15 19 ]. However, according to our knowledge, our present study is the first to assess the serum concentrations of chemokine CXCL12 in relation to its specific receptor CXCR4 and classical tumor markers for EC (CEA and SCC-Ag) as well as marker of inflammatory states—C-reactive protein (CRP).…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Many kinds of chemokine ligands and receptors have been reported to be overexpressed in different types of tumors. [14][15][16][17][18][19] Emerging evidence revealed that elevated expression levels of CXCR4, CXCR5 and CCR7 were relevant to tumorigenesis, cell growth, survival, and sitespecific metastasis. [20][21][22][23][24][25] CXCR4, also known as CD184 or fusin, is a specific chemokine receptor for CXCL12.…”
Section: Introductionmentioning
confidence: 99%